Online Learning Readiness of Junior High School Students in Denpasar - Kadek Erlita Dwiyanti; I Putu Yogi Pratama; Ni Putu Ines Marylena Candra Manik (IJEE (Indonesian Journal of English Education), 2020)
ABSTRACTThe Covid-19 pandemic has caused learning to be carried out online. Not all students, however, are ready for online learning. This study aims to examine the level of readiness of eighth-grade students at a junior high school through an explanatory sequential mixed method design consisting of quantitative and qualitative phases. Student readiness for online learning in this study was reviewed from five dimensions: self-directed learning, motivation for learning, computer/internet self-efficacy, learner control, and online communication self-efficacy. The Online Learning Readiness Scale (OLRS) survey proposed by Hung (2010) with a five-point-Likert scale was used to collect quantitative data. The data were analyzed quantitatively, and the level of readiness was measured utilizing the e-learning readiness assessment model suggested by Aydin and Tasci (2005). Follow-up interviews were then held to support the quantitative data. The results showed that the majority of students entered the level of "ready but needs a few improvements". However, there was one item in the dimension of self-directed learning that was included in the level of "not ready needs some work". The implication of this study is the need to encourage students to actively communicate in online learning, especially for shy students.ABSTRAKPandemi Covid-19 menyebabkan pembelajaran dilakukan secara online. Namun, tidak semua siswa siap dengan pembelajaran online. Penelitian ini bertujuan untuk menguji tingkat kesiapan siswa kelas VIII sebuah sekolah menengah pertama melalui penelitian explanatory sequential mixed method yang terdiri dari tahap kuantitatif dan kualitatif. Kesiapan siswa untuk pembelajaran online ditinjau dari lima dimensi: pembelajaran mandiri, motivasi belajar, efikasi diri komputer / internet, kontrol peserta didik, dan efikasi diri komunikasi online. Survei Online Learning Readiness Scale (OLRS) yang digagas oleh Hung (2010) dilengkapi dengan skala Likert lima poin digunakan untuk mengumpulkan data kuantitatif. Data kemudian dianalisis dengan menggunakan analisis deskriptif kuantitatif dan tingkatannya diukur dengan model penilaian kesiapan E-learning yang dikemukakan oleh Aydin dan Tasci (2005). Wawancara kemudian dilakukan untuk mengumpulkan data guna mendukung data kuantitatif. Hasil penelitian menunjukkan bahwa secara keseluruhan siswa memasuki level “siap, tetapi perlu sedikit perbaikan”. Namun, ada satu item dalam dimensi pembelajaran mandiri yang termasuk dalam tingkat "belum siap, perlu peningkatan". Implikasi dari penelitian ini adalah perlunya mendorong siswa untuk aktif berkomunikasi dalam pembelajaran online, khususnya bagi siswa yang pemalu.